Analisis kualitas pelayanan terhadap kepuasan konsumen dalam pembelian ayam goreng di “Ayam Goreng Roker” di Malang - Mohammad Fuaduzzaki Khoirurrohman; Budi Hartono; Hari Dwi Utami (Faculty of Animal Science, Universitas Brawijaya, 2015)
Study was conducted at “Ayam Goreng Roker” Bratan Lake Street C2 A11 and North Branch Sulfat Street 38 Malang. The purpose of this research was to determine customer satisfaction on quality services and factors that influence customer’s satisfaction on purchasing fried chicken. One hundred respondents were selected by accidental sampling method. Data were collected from 12th September to 12th October 2014. Primary data were collected using questionnaire. Secondary data were obtained from Ayam Goreng Roker’s archives and related sources. The study found that consumer satisfaction was represented by repeating buying, recommended to others of cheaper price, the appropriateness between packages and product, and fried chicken positive images. Consumer satisfaction increased as the availability of service quality including “skill of service and purchasing access”, “worker’s skill”, “feasibility of location and worker’s appearance”, and also “parking facility”. Whereas “feasibility of product, location and service” and “administration” were highly satisfying consumer in purchasing fried chicken. Keywords : worker’s skill, parking facility, access, administration